Temuan insidental lesi radiopak asimptomatik pada pemeriksaan radiografi panoramik: laporan 3 kasus dan ulasan pustaka Dense Bone Island (DBI) - Fadhlil Ulum Abdul Rahman; Lusi Epsilawati; Farina Pramanik; Mirna Febriani (Ikatan Radiologi Kedokteran Gigi Indonesia, 2019)
Objectives: Dense Bone Island (DBI) is one of the lesions that are usually visualized on a panoramic radiographs in the form of total radiopaque in the periapical area of the mandibular premolar or molar but most of them are not directly related to the dentition. This case report is aimed to give summaries about the description of 3 DBI cases. Case Report: Three panoramic radiographs of patients with asymptomatic well-defined radiopaque lesions which was found incidentally in the periapical area of the left mandibular first premolar with two of them showing the lesions located exactly in the 1/3 apical of the root and one of them seen as root resorption like. From clinical information, all three cases reported no clinical symptoms and affected teeth are still vital. Conclusion: Incidental findings of well-defined radiopaque lesion in the periapical area of the premolar and molar of mandible that mostly do not damage the surrounding teeth lead to the diagnosis of dense bone island.